VD_FINDINFO Jug / 2016 / 462 vom 9. Februar 2016 - VD Tribunal cantonal (2016)
GESTION DÉLOYALE, FAUX INTELLECTUEL DANS LES TITRES, USAGE DE FAUXDROIT PÉNAL, SPÉCULATION, OPÉRATION BOURSIÈRE | 158 CP, 251 CP, 42 al. 1 CP, 47 CP